Land Degradation and Climate Change in Africa - African Group of Negotiators Expert Support (2020)
Land degradation is rampant in Africa, accounting for 46% of the total land area. Land degradation at the current pace is projected to render more than half of the cultivated land in Africa unusable by 2050. Land degradation and climate change mutually reinforce each other, creating serious implications for food security, biodiversity and livelihoods in Africa. Effective early warning systems are an essential and important alert mechanism for addressing land degradation. An integrated landscape approach is a promising way to address the broad and multi-faceted nature of land degradation across Africa’s different agro-ecological zones.